PERILAKU SOSIAL WANITA RAWAN SOSIAL TERKAIT DENGAN NORMA, ETIKA DAN ESTETIKA LINGKUNGAN DI PRUMPUNG - FITRIA PITRI FITRIA (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2019)
Abstract This study aims to describe the views of the public towards Social Vulnerable Women (SVW) related to norms, ethics, and environmental aesthetics, orientation and patterns of education dissemination in the SVW family, as well as the impact of implementing education on reproductive prostitution for SVW children. This research was conducted using a qualitative approach. The subjects used in this study were four SVW families consisting of children who went to school and did not attend school as well as mothers who worked as SVW, residents living in the Prumpung area. The results of this study show that as migrants who worked as SVW in Prumpung, they were maintaining their behavior with local residents. Although the work they do is contrary to norms, ethics, and environmental aesthetics. As SVW all their lives, they want to get out of that dark life. Second, people's views on SVW's social behavior in Prumpung are related to the norms, ethics and environmental aesthetics of Prumpung. The community around the beginning did not like the presence of the SVW, but over time the people or natives finally accepted their existence. This is evidenced by the establishment of rented houses, restaurants and taxibike services to service SVW. Third, the factors that support SVW's social behavior related to norms, ethics and environmental aesthetics include increasing economic needs and the lack of education they have.